2021
DOI: 10.1073/pnas.2025865118
|View full text |Cite
|
Sign up to set email alerts
|

Precision mapping child undernutrition for nearly 600,000 inhabited census villages in India

Abstract: There are emerging opportunities to assess health indicators at truly small areas with increasing availability of data geocoded to micro geographic units and advanced modeling techniques. The utility of such fine-grained data can be fully leveraged if linked to local governance units that are accountable for implementation of programs and interventions. We used data from the 2011 Indian Census for village-level demographic and amenities features and the 2016 Indian Demographic and Health Survey in a bias-corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…One issue with the NNS, however, is its explicit focus on districts. In the context of child malnutrition, some of the geographic variation is attributable to between-district differences (13), while other studies have shown that a larger share of the variation is attributable to states (14,15) and villages (16)(17)(18), a consequence of the geographic clustering of risk factors (19). Recent studies have also elucidated the small area variation of anthropometric failure within districts.…”
Section: Introductionmentioning
confidence: 99%
“…One issue with the NNS, however, is its explicit focus on districts. In the context of child malnutrition, some of the geographic variation is attributable to between-district differences (13), while other studies have shown that a larger share of the variation is attributable to states (14,15) and villages (16)(17)(18), a consequence of the geographic clustering of risk factors (19). Recent studies have also elucidated the small area variation of anthropometric failure within districts.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing solely on the district-level estimates overlooks any small area variation within districts in the reported outcomes, as anemia prevalence at different geographical levels (states, districts, villages) can differ significantly depending on the area. Recent research shows that in the case of anthropometric failures such as stunting, geographic variation attributable to states ( 13 , 14 ), and villages ( 15 17 ) is much higher than variation between districts. ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] The program’s scale is huge – it covers every village in the country’s 36 states and union territories. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%